Role of Psychological Capital in Moderating the Influence of Employee Engagement and Creativity on the Performance of Nursing Staff at Class a Regional Hospitals in East Kalimantan Province, Indonesia - Mualimin, Jaya; Setyadi, Djoko; Zainurossalamia, Saida; Kuleh, Johanes; Aziz, Abdul (Journal of Management World, 2025)
This study aims to analyze the impact of employee engagement on organizational performance in government hospitals, with particular attention to the moderating role of Psychological Capital – comprising resilience, optimism, self-efficacy, and hope - in strengthening this relationship. Grounded in theories of employee engagement and Positive Organizational Behavior, this research positions Psychological Capital as a critical construct that enhances an individual’s motivational and cognitive resources. By integrating these theoretical perspectives, the study elucidates how engagement and Psychological Capital jointly influence performance outcomes. Using a quantitative research design, data were collected via structured surveys from hospital employees in various administrative and clinical departments. Statistical analyses were then conducted to assess the direct influence of employee engagement on performance, as well as the interaction effect (moderation) of Psychological Capital. Findings confirm that employee engagement has a significant positive effect on performance, underscoring the importance of motivational and supportive work environments in government hospitals. Moreover, the moderating role of Psychological Capital is evident, as higher levels of resilience, optimism, self-efficacy, and hope substantially strengthen the engagement–performance linkage. These results underscore the necessity of strategies - such as organizational learning programs, clear alignment with the hospital's vision and mission, and active employee participation - to cultivate both engagement and Psychological Capital. By highlighting the combined importance of engagement and Psychological Capital, this study offers practical insights for hospital management to refine human resource strategies. Interventions designed to enhance Psychological Capital can bolster engagement, thereby improving service quality and operational efficiency, ultimately contributing to better patient outcomes. While previous research has established the positive association between engagement and performance, this study uniquely contributes by empirically testing the moderating role of Psychological Capital within the government hospital context. The findings offer a novel framework for developing targeted interventions that elevate employee motivation, well-being, and organizational success in a setting marked by administrative challenges and resource constraints.